Chemokines and 'bath salts': CXCR4 receptor antagonist reduces rewarding and locomotor-stimulant effects of the designer cathinone MDPV in rats. (1st May 2018) - Oliver, Chicora F.; Simmons, Steven J.; Nayak, Sunil U.; Smith, Garry R.; Reitz, Allen B.; Rawls, Scott M.
Highlights: A role for CXCL12/CXCR4 in designer cathinone (MDPV) pharmacology was investigated. AMD3100 reduced MDPV-induced locomotor activation. AMD3100 reduced MDPV-induced conditioned place preference. AMD3100 modulated MDPV-induced increase in 50 k-Hz USV calls. MDPV rewarding and stimulant efficacy requires active CXCR4 receptors. Abstract: Background and purpose: Little is known about how chemokine systems influence the behavioral effects of designer cathinones and psychostimulants. The chemokine CXCL12 and its principal receptor target, CXCR4, are of particular interest because CXCR4 activation enhances mesolimbic dopamine output that facilitates psychostimulant reward, reinforcement, and locomotor activation. Repeated cocaine enhances CXCL12 gene expression in the midbrain and produces conditioned place preference (CPP) that is inhibited by a CXCR4 antagonist. Yet, interactions between chemokines and synthetic cathinones remain elusive. Methods: We tested the hypothesis that an FDA-approved CXCR4 antagonist (AMD3100) inhibits MDPV-induced reward, locomotor activation and positive affective state in rats using a triad of behavioral assays (CPP, open field, and 50-kHz ultrasonic vocalizations [USVs]). Key results: AMD3100 (1, 2.5, 5, 10 mg/kg, ip) significantly reduced MDPV (2 mg/kg, ip)-evoked hyper-locomotion in a dose-related manner. AMD3100 (1, 5, 10 mg/kg) administered during CPP conditioning caused a significant, dose-dependent reduction of MDPV (2 mg/kg x 4 days) place preference. MDPV injection elicited significantly greater 50 kHz USVs in vehicle-pretreated rats but not in AMD3100-pretreated rats. Conclusion and implication: A CXCR4 antagonist reduced the rewarding and locomotor-activating effects of MDPV. Our results identify the existence of chemokine/cathinone interactions and suggest the rewarding and stimulant effects of MDPV, similar to cocaine, require an active CXCL12/CXCR4 system.